2014
DOI: 10.5688/ajpe78483
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of E-learning in Pharmacy Education

Abstract: Over the past 2 decades, e-learning has evolved as a new pedagogy within pharmacy education. As learners and teachers increasingly seek e-learning opportunities for an array of educational and individual benefits, it is important to evaluate the effectiveness of these programs. This systematic review of the literature examines the quality of e-learning effectiveness studies in pharmacy, describes effectiveness measures, and synthesizes the evidence for each measure. E-learning in pharmacy education effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(154 citation statements)
references
References 42 publications
8
143
0
3
Order By: Relevance
“…In postgraduate residents in surgery, medicine, gynaecology and obstetrics high initial scepticism concerning eLearning (76.4%) was contrasted by high satisfaction rates after the eLearning experience (64.8%) and the majority of residents rated eLearning as better than traditional learning methods (61.8%) [23]. The above-mentioned randomised study among primary care physicians revealed similarly high satisfaction rates for eLearning and traditional learning methods, which is in agreement with most of the literature on this topic [39]. A large study with several thousand Scottish trainees reviewed the use of eLearning modules over an academic year.…”
Section: Satisfaction With Elearningsupporting
confidence: 77%
See 1 more Smart Citation
“…In postgraduate residents in surgery, medicine, gynaecology and obstetrics high initial scepticism concerning eLearning (76.4%) was contrasted by high satisfaction rates after the eLearning experience (64.8%) and the majority of residents rated eLearning as better than traditional learning methods (61.8%) [23]. The above-mentioned randomised study among primary care physicians revealed similarly high satisfaction rates for eLearning and traditional learning methods, which is in agreement with most of the literature on this topic [39]. A large study with several thousand Scottish trainees reviewed the use of eLearning modules over an academic year.…”
Section: Satisfaction With Elearningsupporting
confidence: 77%
“…A systematic review from 2014 on eLearning in pharmacy education concluded that it effectively increases knowledge of physicians and students. However, there was no evidence that eLearning effectively improved skills or professional practice, and the need for long-term studies following on from knowledge gain was pointed out [39]. In undergraduate medical training, a 2014 systematic review including 4955 students found that eleven out of 33 studies testing knowledge gains found higher gains in the eLearning groups.…”
Section: Efficacy Of Elearning On Postgraduate Neurosurgery Trainingmentioning
confidence: 99%
“…9 Student perception on e-learning can be measured through their belief on the benefits of e-learning, relevance of the e-learning content, and e-learning functionality. 32 In terms of the benefits, it can be assessed through their thoughts on the knowledge gained, confidence, stimulant interest, and usefulness of online discussions. In terms of the relevance of e-learning content, a study was done on university students of OUM, UNITAR, and International Islamic University showing that the majority of students are satisfied with the content as long as it is well organized and easy to understand.…”
Section: Students and Teachers' Perceptions Towards E-learningmentioning
confidence: 99%
“…This indicates that e-learning does leave positive changes in the knowledge gained.However, there is no significant difference of the knowledge gained by e-learning method or traditional learning method. 32 As for students' skills, it can be assessed by using rating scale, search skill test, Likert-type questionnaire, and written assessments such as data collection sheets.…”
Section: Impact Of E-learningmentioning
confidence: 99%
“…[15][16][17][18][19] In the field of substance misuse, online education for pharmacists has been developed and evaluated in New Zealand. 20 The approach replaced a 3-4 hour training session and resulted in improved attitudes of trained community pharmacists toward patients receiving OST, as well as improvements in confidence and skills.…”
Section: Introductionmentioning
confidence: 99%